Peran Kantor Dagang dan Ekonomi Indonesia (KDEI) Taipei dalam Penyelesaian Masalah Pekerja Migran Indonesia (PMI) Sektor Informal di Taiwan Tahun 2022-2023 - Aini, Saffana Qurratul; Kasanusi; Iskandar, Winda Nurlaily Rafikalia (Frequency of International Relations (FETRIAN), 2026)
This research specifically focuses on the role of the Indonesian Economic and Trade Office (IETO) in Taipei in addressing issues faced by Indonesian Migrant Workers (PMI) in Taiwan's informal sector—a subject not yet deeply explored in prior research, despite the fact that this group often encounters more complex challenges. The study aims to analyze IETO Taipei’s role in resolving the problems faced by informal-sector migrant workers in Taiwan during the 2022–2023 period, utilizing soft power theory and a humanitarian diplomacy approach. A qualitative descriptive method was employed, incorporating life history analysis and a case study approach. Data collection relied on secondary sources, including the official websites of IETO Taipei and the Indonesian Migrant Workers Protection Agency (BP2MI), as well as relevant official documents and scholarly journals. The findings indicate that IETO Taipei plays a strategic role in resolving issues affecting informal-sector migrant workers through negotiation, coordination, and advocacy grounded in soft power and humanitarian diplomacy.